FINANCIAL REPORTING AS PART OF THE SYSTEM OF INFORMATION SUPPLY OF MODERN ENTERPRISE MANAGEMENT - Shubina , Svitlana; Miroshnyk, Oleksii; Rudenko, Alona; Karapetyan, Ruzanna; Shevchuk, Dmytro (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2021)
This article presents financial statements as the main source of information support of modern business management. It is noted that financial reporting is a set of reporting forms, compiled on the basis of financial accounting data in order to provide external and internal users with generalized information about the financial condition of the enterprise in a convenient and understandable way for these users to take certain business decisions. The main aspects of accounting information, which serves as information support for making management decisions, are determined in this article. Attention is focused on the importance of internal reporting, which is formed at the enterprise with the purpose of operative provision of objective management information in order to satisfy information needs of internal users, whose management decisions significantly affect the results of enterprise activities. It considers and summarizes the theoretical aspects of the adaptation of financial reporting in Ukraine in accordance with the terms, principles and requirements of International Financial Reporting Standards. It is noted that the choice of methods of IFRS reporting depends first of all on the purposes of further use, periodicity of preparation, qualification of specialists. The advantages and disadvantages of parallel accounting, which makes possible to promptly generate reports according to international standards for the needs of both internal and external users, are determined. Considering the importance of accounting policy as a set of rules adopted by the enterprise for the preparation and presentation of financial statements, a list of the main sections of the Order on Accounting Policy is provided in this article. Also, the article considers and summarizes the main features of the presentation of information in the financial statements according to international standards, which characterize it as accessible to a wide range of consumers and allow making objective and balanced management decisions.